MARKET STRUCTURE IN ISLAMIC PERSPECTIVE: A CRITICAL EXAMINATION OF THE TERMS PERFECT AND IMPERFECT COMPETITION - Sri Yayu Ninglasari; M. Fikri Himmawan; Luthfi Nur Rosyidi; Aas Nur Asyiah (Universitas Muhammadiyah Surabaya, 2023)
The purpose of this study is to examine the terms